Rapid Sequence Intubation in the ER Using Video Laryngoscopy and Direct Laryngoscopy (American Journal of Medical Science and Innovation, 2025)
Endotracheal intubation, or EI, is a common procedure in the ICU, particularly for critically ill patients who require mechanical ventilation or airway compromise. This patient population presents unique challenges, including anatomic conditions, physiologic factors, logistics, and operator experience. The objective of the systematic was to assess the efficacy of video laryngoscopy compared to direct laryngoscopy in rapid sequence intubation procedures, particularly in intensive care units, intending to evaluate various outcomes such as laryngeal visualization, intubation success rates, time to intubation, and other complications. Systematic review and meta-analysis of nineteen have been conducted according to PRISMA guidelines, sourcing articles from January 2005 to February 2023 across databases like PubMed and Google Scholar. Studies in English comparing video laryngoscopy and direct laryngoscopy for rapid sequence intubation were included. Quality assessment adhered to Cochrane risk of bias guidelines, and the meta-analysis utilized a Mantel-Haenszel random-effect model with a 95% confidence interval for precision. The results concluded that VL exhibited higher first-attempt intubation success rates than DL, but no significant differences were observed in overall success rates. Time to intubation showed a slight reduction with VL compared to DL, while complications such as hypotension and dental trauma were moderately higher with VL. In summary, the utilization of VL in rapid sequencing intubation has been linked to a reduced time to achieve successful intubation compared to DL. However, additional analysis, such as hospital duration of stays, follow-up time, and monitoring of adverse events, has been necessary for a thorough meta-analysis.